(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
The article discusses the consideration of slope orientations and inclinations, which are components of the relief of the Ararat Basin, in the planning and implementation of military operations. With their effective application, military infrastructures and communication routes can be located in relatively safe places, on opposite slopes protected from the enemy’s fire. On the maps compiled by the authors at a scale of 1:1 000 000, the orientations and inclinations of the Ararat Basin, the distribution regions and surfaces of all orientations and inclinations are calculated. Their correct use for military purposes is discussed, especially during the movement of mechanized military units and subunits. The work also discusses the intensity of slope, washing in different slopes and inclinations of orientation, where slope erosion and landslide phenomena are activated. The movement of heavy equipment is particularly dangerous in the areas of their distribution. The work is summarized with corresponding conclusions and recommendations.